Financial Crisis, Organizational Behavior and Organizational Silence in the Public Sector: A Case Study for Greece - Paraskevi Boufounou; Kallirroi Avdi (SPOUDAI - Journal of Economics and Business, 2016)
The present article presents the empirical findings of a questionnaire survey carried out in Greece, exploring the effects of the recent financial crisis on organizational behavior in the country's public sector. The study focuses on the impact of the financial crisis on organizational management and more specifically on the evolution of "organizational silence", taking into account public servants' hierarchical position, gender, education and skills. Based on the evidence provided, it is concluded that organizational silence is likely to have negative long-run repercussions for public sector productivity.
Keywords: M10; M21; M54; 650; Human Resource Management; Organizational Silence; Organizational Behavior; Financial Crisis; Gender Issues